Synthesis and biological activity of 5-(4-methoxyphenyl)-oxazole derivatives. Issue 2 (15th January 2015) - Yamamuro, Daisuke; Uchida, Ryuji; Ohtawa, Masaki; Arima, Shiho; Futamura, Yushi; Katane, Masumi; Homma, Hiroshi; Nagamitsu, Tohru; Osada, Hiroyuki; Tomoda, Hiroshi
Graphical abstract: Abstract: 5-(4′-Methoxyphenyl)-oxazole (MPO), originally reported as a synthetic compound, was isolated from fungal culture broth as an inhibitor of hatch and growth of Caenorhabditis elegans. Nineteen MPO derivatives were chemically synthesized, but showed no effect on C. elegans hatch and growth. These findings strongly suggested that the whole structure of MPO is essential for anti- C. elegans activity.